Predictive role of erythrocyte macrocytosis during treatment with pemetrexed in advanced non-small cell lung cancer patients. Issue 3 (June 2015) - Buti, Sebastiano; Bordi, Paola; Tiseo, Marcello; Bria, Emilio; Sperduti, Isabella; Di Maio, Massimo; Panni, Stefano; Novello, Silvia; Rapetti, Simonetta Grazia; Pilotto, Sara; Genestreti, Giovenzio; Rossi, Antonio; et al.
Highlights Pemetrexed based chemotherapy is a standard for advanced non-small cell lung cancer. Clinical and laboratory data were retrospectively obtained from 191 patients. All patients were treated with pemetrexed based chemotherapy. Pemetrexed increased mean corpuscular volume (MCV). The MCV increment correlated with better DCR, PFS and OS.